Financial Analysis of Cattle Production in the Cooperative Integrated Agribusiness in Subak Guama Tabanan Regency - PRADNYANI, NI PUTU ROSY; YUSUF, RIA PUSPA; YUDHARI, DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.3, No.1, Januari 2014, 2014)
ABSTRACT Financial Analysis of Cattle Production in the Cooperative Integrated Agribusiness in Subak Guama Tabanan Regency The prospects of entrepreneur in  Bali every year  is very bright since there is an increase demand for beef Bali. The purpose of this study is to determine the feasibility of Bali cattle managed by cooperatives Subak Guama financially and to identify the constraints faced in implementing  cattle fattening. The choice of location in this study using purposive sampling method on feedlot Balinese. Once all the required data collected, then analyzed using investment criteria are: NPV, Net B / C Ratio, IRR and sensitivity analysis. The study found that NPV = 13.115.654,93; B/C Ratio = 1,10; IRR = 2.667.924,53 and Sensitivity Analysis found that  NPV = 7.815.750,31; BC Ratio = 1,05; IRR = 1.355.283,00 if the total cost increase. NPV = -22.677.658,61; BC Ratio = 0,77; IRR = -6.128.301,89 if the gross benefit decrease. The problem faced economic problem and social problem. With the establishment of  the Cooperatives there is  a positive impact for the community Batannyuh village, such as  the number of people who become employees of the Cooperative, and avoiding farmers from debt bondage system, which allows farmers to sell their crops to the Cooperatives, there by increasing farmers' income. Efforts can be made ??by  the cooperatives to increase livestock production by seeking manufacturing cows themselves that the cost of purchasing the seeds can be saved. In addition, to increase the income of farmers, the farmer should grow their own forage,so that production costs could be minimized. Keywords : financial, production, agribusiness
Keywords: financial, production, agribusiness